Carverovci, altmanovci, ''prljavi'' i "sudoperski'' realisti i još pokoji realizam suvremene skandinavske proze - Tomić, Janica (Array, 2009)
The paper deals with prose and film texts that have emerged from the 1980s onwards in Scandinavia and elsewhere under various ’ realist’ coinages and on the wave of, what is most commonly defined as Shortcuts’ (R. Carver and R. Altman’ s) inspired storytelling. The first segment outlines these tendencies in literature, especially the upsurge of interest in short stories (Swedish novellboom etc.), and comments on interpretative strategies that predominantly place such trends within a broader context of Carverian writing. The second part analyzes the proliferation of Altmanesque short story cycles, such as Frode Gryttens Song of the Beehive, with the help of Bordwell’ s notion of network narratives, and establishes intermedial links with synchronically and narratively adjacent Hollywood and other films.